Missions and empire - Etherington, Norman (Oxford ; New York : Oxford University Press, 2005)
The explosive expansion of Christianity in Africa and Asia during the last two centuries constitutes one of the most remarkable cultural transformations in the history of mankind. Because it coincided with the spread of European economic and political hegemony, it tends to be taken for granted that Christian missions went hand in hand with imperialism and colonial conquest. In this book historians survey the relationship between Christian missions and the British Empire from the 17th century to the 1960s and treat the subject thematically, rather than regionally or chronologically. Many of these themes are treated at length for the first time.--Book jacket
Prelude : the Christianizing of British America / Eliga H. Gould -- An overview, 1700-1914 / Andrew Porter -- Humanitarians and white settlers in the nineteenth century / Alan Lester -- Where the missionary frontier ran ahead of empire / John Barker -- Christian missions and the Raj / Robert Eric Frykenberg -- New Christians as evangelists / Peggy Brock -- '"Trained to tell the truth" : missionaries, converts, and narration / Gareth Griffiths -- Women and cultural exchanges / Patricia Grimshaw and Peter Sherlock -- Language / Paul Landau -- New religious movements / Rober Edgar -- Anthropology / Patrick Harries -- Education and medicine / Norman Etherington -- Decolonization / David Maxwell
Includes bibliographical references and index
Keywords: Missions, British -- History; Christianity and politics -- Colonies -- Great Britain -- History; Imperialism -- History; Great Britain -- Colonies -- Religion